Smärta, skönhet och sociomaterialitet: En intervju med Dag Østerberg om begreppen form, förändring och socialitet (Sociologisk Forskning, 2009)
Pain, beauty, and socio-matter. An interview with Dag Østerberg concerning the concepts of form, process, and sociality.Professor Dag Østerberg (born 1938) is one of the most prominent Nordic sociologists and the author of many influential books. In this interview he discusses the concept of form in sociology and social thinking and relates it not only to change, but to sociality, pain, beauty, and socio-matter as well. In order to contextualise Østerberg’s discussion, the interview is prefaced by a brief introduction to the traditional understanding of form as related to matter and content.